2005
DOI: 10.1021/jp046312w
|View full text |Cite
|
Sign up to set email alerts
|

The Stokes−Einstein Relationship and the Levitation Effect: Size-Dependent Diffusion Maximum in Dense Fluids and Close-Packed Disordered Solids

Abstract: We report a molecular dynamics study of a binary mixture consisting of a large (host) particle and a smaller (guest) particle whose radius is varied over a range. These simulations investigate the possible existence of a diffusion anomaly or levitation effect in dense fluids, previously seen for guest molecules diffusing within porous solids. The voids in the larger component have been characterized in terms of void and neck distributions by means of Voronoi polyhedral analysis. Four different mixtures with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
71
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(82 citation statements)
references
References 38 publications
11
71
0
Order By: Relevance
“…The theory and simulation studies both predict that as the solute size is decreased the diffusion value first increases and then decreases. This diffusivity maximum as discussed earlier has been attributed to levitation effect [9]. Thus it is found that MCT can predict levitation effect and diffusivity maximum as found in simulations [9] and experimental [17] studies.…”
Section: Resultssupporting
confidence: 74%
See 4 more Smart Citations
“…The theory and simulation studies both predict that as the solute size is decreased the diffusion value first increases and then decreases. This diffusivity maximum as discussed earlier has been attributed to levitation effect [9]. Thus it is found that MCT can predict levitation effect and diffusivity maximum as found in simulations [9] and experimental [17] studies.…”
Section: Resultssupporting
confidence: 74%
“…As mentioned in the Introduction, this anomalous size dependence of diffusion has been attributed to levitation effect [9] where the solute particles with intermediate sizes are expected to levitate through the neck of the solvent cage whereas the smaller particles are expected to be strongly attracted to one solvent particle. Fig.1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations